On the performance of a hybrid process to mineralize the herbicide tebuthiuron using a DSA (R) anode and UVC light: A mechanistic study - Montes, Isaac J. S.; Silva, Bianca F. [UNESP]; Aquino, Jose M. (Elsevier B.V., 2017)
A hybrid electrochemical and photochemical (HEP) process was used to oxidize and mineralize the herbicide tebuthiuron (TBT), which is a potential contaminant of ground water, using a DSA (R) anode and UVC light. The electrochemical and photochemical experiments were carried out in flow reactors and the investigated variables were: i) power of the Hg lamp (5, 9, 80, and 125 W), ii) solution pH (3, 7, 11, and no control), iii) NaCl concentration (0, 1, 2, and 4 g L-1), and iv) electric current density (10, 20, and 30 mA cm(-2)). The performance of the oxidation and mineralization process of TBT and its intermediates was assessed by high performance liquid chromatography coupled to mass spectrometry and total organic carbon analyses. The use of a 9 W Hg lamp led to complete oxidation and mineralization of TBT, and its intermediate compounds, from acidic to neutral solutions, independently of the applied electric current density, and with increasing NaCl concentration. High CO2 conversions were obtained using the HEP process, as the generated intermediates (including an organochlorine) were completely eliminated. TBT removal rates similar to those of an electrochemical experiment using a boron-doped diamond anode were attained using the HEP process, but with higher energy consumption; however, chlorinated carboxylic acids were no longer present in the final treatment stages. The HEP process could be regarded as an advanced oxidation process, being an interesting option to treat effluents contaminated with organics if a proper optimization of the UVC lamp is done. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Mediated oxidation; Synergistic effect; Synthetic organic pollutants; Organochlorine compounds; Mixed oxide anode